School museum of combat glory of the 75th Guards brigade: history, experience and importance of patriotic work - A. V. Sushko; N. V. Leader (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the history of the creation and development from the founding in 1973 to the present day of the School Museum of Military Glory of the 75th Guards Brigade, located in the Secondary School of the city of Omsk No. 41. The research was carried out on the basis of museum materials and documents of the veteran organization of the military unit, stored in the Historical archive of the Omsk Region. An assessment of the experience and social significance of the patriotic work carried out in the museum is given. Particular attention is paid to the comparative historical study of the forms of work on the patriotic education of youth in the Soviet and modern Russian periods of national history. In conclusion, recommendations are given for improving the work of the museum.